Distinguishing exercise intolerance in early‐stage pulmonary hypertension with invasive exercise hemodynamics: Rest VE/VCO2 and ETCO2 identify pulmonary vascular disease. Issue 7 (14th April 2022) - Raza, Farhan; Dharmavaram, Naga; Hess, Timothy; Dhingra, Ravi; Runo, James; Chybowski, Amy; Kozitza, Callyn; Batra, Supria; Horn, Evelyn M.; Chesler, Naomi; Eldridge, Marlowe
Abstract: Background: Among subjects with exercise intolerance and suspected early‐stage pulmonary hypertension (PH), early identification of pulmonary vascular disease (PVD) with noninvasive methods is essential for prompt PH management. Hypothesis: Rest gas exchange parameters (minute ventilation to carbon dioxide production ratio: V E / V CO2 and end‐tidal carbon dioxide: ETCO2 ) can identify PVD in early‐stage PH. Methods: We conducted a retrospective review of 55 subjects with early‐stage PH (per echocardiogram), undergoing invasive exercise hemodynamics with cardiopulmonary exercise test to distinguish exercise intolerance mechanisms. Based on the rest and exercise hemodynamics, three distinct phenotypes were defined: (1) PVD, (2) pulmonary venous hypertension, and (3) noncardiac dyspnea (no rest or exercise PH). For all tests, * p < .05 was considered statistically significant. Results: The mean age was 63.3 ± 13.4 years (53% female). In the overall cohort, higher rest V E / V CO2 and lower rest ETCO2 (mm Hg) correlated with high rest and exercise pulmonary vascular resistance (PVR) ( r 0.5–0.6*). On receiver‐operating characteristic analysis to predict PVD (vs. non‐PVD) subjects with noninvasive metrics, area under the curve for pulmonary artery systolic pressure (echocardiogram) = 0.53, rest V E / V CO2 = 0.70* and ETCO2 = 0.73*. Based on this, optimal thresholds of rest V E / V CO2 > 40 mm Hg and rest ETCO2 < 30 mm Hg were applied to the overall cohort. Subjects with both abnormal gas exchange parameters ( n = 12, vs. both normal parameters, n = 19) had an exercise PVR 5.2 ± 2.6* (vs. 1.9 ± 1.2), mPAP/CO slope with exercise 10.2 ± 6.0* (vs. 2.9 ± 2.0), and none included subjects from the noncardiac dyspnea group. Conclusions: In a broad cohort of subjects with suspected early‐stage PH, referred for invasive exercise testing to distinguish mechanisms of exercise intolerance, rest gas exchange parameters ( V E / V CO2 > 40 mm Hg and ETCO2 < 30 mm Hg) identify PVD.